2022
DOI: 10.3389/fphar.2022.829830
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Promotes Differentiation and Attenuates H2O2-Induced Oxidative Damage of Osteoblasts via the PI3K/AKT/Nrf2/HO-1 Pathway

Abstract: At present, the drug treatment of osteoporosis is mostly focused on inhibiting osteoclastogenesis, which has relatively poor effects. Metformin is a drug that can potentially promote osteogenic differentiation and improve bone mass in postmenopausal women. We aimed to detect the molecular mechanism underlying the osteogenic effect of metformin. Our study indicated that metformin obviously increased the Alkaline phosphatase activity and expression of osteogenic marker genes at the mRNA and protein levels. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Our previous study also showed that Nrf2 activation attenuated cardiac damage after myocardial infarction injury, whereas AKT inhibition almost abolish the effect of Nrf2 [39]. It is worth noting that metformin is an effective Nrf2 activator, and the effect is tightly related to activation of AKT [40,41]. These results lead us to hypothesize that metformin might elicit similar effect in ethanol-treated cardiomyocytes.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous study also showed that Nrf2 activation attenuated cardiac damage after myocardial infarction injury, whereas AKT inhibition almost abolish the effect of Nrf2 [39]. It is worth noting that metformin is an effective Nrf2 activator, and the effect is tightly related to activation of AKT [40,41]. These results lead us to hypothesize that metformin might elicit similar effect in ethanol-treated cardiomyocytes.…”
Section: Discussionmentioning
confidence: 70%
“…Metformin reverses pre-osteoblast mitochondrial dysfunction by attenuating mPTP opening. Based on a previous study by the authors, 0.2 mM was determined to be the optimal concentration of H 2 O 2 to induce oxidative stress in pre-osteoblasts, which reached the maximum apoptotic rate (22). In addition, 0.2 mM metformin was shown to have the strongest ability to reverse oxidative apoptosis (22).…”
Section: Resultsmentioning
confidence: 97%
“…Based on a previous study by the authors, 0.2 mM was determined to be the optimal concentration of H 2 O 2 to induce oxidative stress in pre-osteoblasts, which reached the maximum apoptotic rate ( 22 ). In addition, 0.2 mM metformin was shown to have the strongest ability to reverse oxidative apoptosis ( 22 ). The present study first examined the mechanisms by which metformin prevents pre-osteoblast apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, bone tissue is in a dynamic balance between the bone formation effect of osteoblasts and the bone resorption effect of osteoclasts ( Teissier et al, 2022 ). The direct pathogenesis of osteoporosis is that the weakened bone formation is difficult to compensate for the reduced bone mass of bone resorption ( Yang et al, 2022 ). With aging, the prevalence of osteoporosis is increasing year by year ( Dong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%